2020
DOI: 10.1177/0363546520926448
|View full text |Cite
|
Sign up to set email alerts
|

A Word of Caution for Future Studies in Patellofemoral Pain: A Systematic Review With Meta-analysis

Abstract: Background: Patellar maltracking is widely accepted as an underlying mechanism of patellofemoral pain. However, methodological differences in the literature hinder our ability to generate a universal quantitative definition of pathological patellofemoral kinematics (patellar maltracking) in patellofemoral pain, leaving us unable to determine the cause of patellofemoral pain. Purpose: To systematically review the literature to provide evidence regarding the influence of confounding variables on patellofemoral k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
(166 reference statements)
1
10
0
Order By: Relevance
“…As such, it is crucial that future studies clearly define the axial plane used to measure LTI so that results can be directly compared across studies. The reduced trochlear width and depth, 5 patella alta, 6 lateralized patella, 15 and increased TT-TG 6,47 all agree with findings of past reports. Direct reporting of the medial and lateral trochlear length could not be found; however, our results agree with the increased patellar trochlear ratio previously reported.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As such, it is crucial that future studies clearly define the axial plane used to measure LTI so that results can be directly compared across studies. The reduced trochlear width and depth, 5 patella alta, 6 lateralized patella, 15 and increased TT-TG 6,47 all agree with findings of past reports. Direct reporting of the medial and lateral trochlear length could not be found; however, our results agree with the increased patellar trochlear ratio previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…5 Similarly, the measures of patellofemoral alignment (shift, tilt, and alta) agreed with those previously reported. 15 The novel measure of anterior patellar displacement needs further study. With a decrease in trochlear depth, a decreased anterior displacement was expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that patellar maltraction causes a high level of mechanical stress on the subchondral bone due to the altered patellofemoral contact, thereby resulting in pain. 3,4 In 2018, the iPFRN published a consensus document concerning PFP management that specified a hip-and knee-focused exercise regimen to be the approach with the highest level of evidence regarding its effectiveness. Moreover, applications such as patellar taping, manual therapy, and foot orthoses are recommended in addition to exercise, albeit not as standalone treatments.…”
Section: Introductionmentioning
confidence: 99%
“…29,27 A meta-analysis demonstrated that the assessment of patellofemoral alignment together with quadriceps activation improves the ability to diagnose maltracking. 17 However, the type (dynamic or static) and intensity of muscle contraction varied among studies. Although several studies have compared the patellofemoral joint alignment in knee extension with and without quadriceps contraction, 5,18 most studies included analysis of the patellofemoral joint alignment without knee motion and with quadriceps isometric contraction.…”
mentioning
confidence: 99%